A disturbed interaction with accessory cells upon opportunistic infection with Pseudomonas aeruginosa contributes to an impaired IFN-γ production of NK cells in the lung during sepsis-induced immunosuppression. Issue 2 (February 2015) - Pastille, Eva; Pohlmann, Stephanie; Wirsdörfer, Florian; Reib, Anna; Flohé, Stefanie B
Impaired resistance to Pseudomonas aeruginosa -induced pneumonia after cecal ligation and puncture (CLP), a mouse model for human polymicrobial sepsis, is associated with decreased IFN-γ, but increased IL-10, levels in the lung. We investigated the so far unknown mechanisms underlying this reduced IFN-γ synthesis in CLP mice. CD11b + NK cells, but not T or NKT cells in the lung were impaired in IFN-γ synthesis upon challenge with Pseudomonas in vitro and in vivo after CLP. The inhibition of NK cells was independent of IL-10. IFN-γ synthesis of NK cells was only partly restored by addition of recombinant IL-12. Accessory cells including dendritic cells and alveolar macrophages were required for maximal IFN-γ secretion. But accessory cells of CLP mice suppressed the IFN-γ secretion from naive lung leukocytes. In turn, naive accessory cells were unable to restore the IFN-γ production from lung leukocytes of CLP mice. Thus, a disturbed interaction of accessory cells and NK cells is involved in the impaired IFN-γ release in response to Pseudomonas in the lung of CLP mice. Considering the importance of IFN-γ in the immune defense against bacteria the dysfunction of accessory cells and NK cells might contribute to the enhanced susceptibility to Pseudomonas after CLP.